2022
DOI: 10.1177/08850666221092687
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Severe COVID-19: Long-Term Outcomes of Patients Admitted to an Intensive Care Unit

Abstract: Background Understanding the long-term sequelae of severe COVID-19 remains limited, particularly in the United States. Objective To examine long-term outcomes of patients who required intensive care unit (ICU) admission for severe COVID-19. Design, Patients, and Main Measures This is a prospective cohort study of patients who had severe COVID-19 requiring an ICU admission in a two-hospital academic health system in Southern California. Patients discharged alive between 3/21/2020 and 12/31/2020 were surveyed ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 60 publications
(62 reference statements)
0
19
1
Order By: Relevance
“… 6 Multiple national and international collaborations have reported outcome data in critically ill patients, 7 , 8 , 9 including long‐term functional outcomes. 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 Multiple national and international collaborations have reported outcome data in critically ill patients, 7 , 8 , 9 including long‐term functional outcomes. 10 …”
Section: Introductionmentioning
confidence: 99%
“…6 Multiple national and international collaborations have reported outcome data in critically ill patients, [7][8][9] including long-term functional outcomes. 10 Our objectives were (a) to evaluate factors on ICU admission associated with 90-day mortality and (b) to describe factors during the ICU stay associated with functional outcomes at 90 days. We hypothesised that high age, body mass index (BMI) and ICU burden were associated with increased 90-day mortality, longer ICU stay and worse functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,20,29 A study that looked at the long-term outcomes of patients who needed ICU admission for severe COVID-19 found that the long-term effects of severe COVID-19 lasted more than six months. 34 Similarly, a 12-month study found that a chest CT scan in acute COVID-19 correlates with pulmonary function and respiratory symptoms after SARS-CoV-2 infection. 35 Obesity, hypertension, diabetes mellitus, and the presence of any chronic illness were all statistically significant predictors of long COVID.…”
Section: Discussionmentioning
confidence: 95%
“…12 Intensive care services were stretched by unprecedented demand, acute staff shortages and high levels of personal protective equipment. 13 Data from previous infective outbreaks, 14 suggest that clinicians may witness an increased incidence of post-ICU psychopathology, following the pandemic. 15 …”
Section: Introductionmentioning
confidence: 99%